White Collar Criminals' Experience of Imprisonment in England and Wales: Revisiting the 'special Sensitivity' Debate. Issue 12 (1st December 2020) - Button, Mark; Gough, Dennis; Shepherd, David; Blackbourn, Dean
ABSTRACT: This article explores white collar criminals' experience of imprisonment in England and Wales. Based upon interviews with 13 convicted offenders after they had completed their imprisonment, it is the first study to date of this kind in England and Wales (all others have been based in prison). It offers a unique impartial insight of prisoners' experience, beyond the influence of the prison walls. The paper explores the experience around the largely American 'special sensitivity' debate, over whether such offenders are more sensitive to prison. The research uncovers both positive experiences, labelled 'good', but also negative, labelled 'bad' (non-violent experiences) and 'ugly' (violent experiences). Overall the findings reveal it is difficult to apply the special sensitivity hypothesis universally to this group of offenders.